2011
DOI: 10.1111/j.1742-4658.2011.08308.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of HoxE subunit in Synechocystis PCC6803 hydrogenase

Abstract: Cyanobacterial NAD(P) + -reducing reversible hydrogenases comprise five subunits. Four of them (HoxF, HoxU, HoxY, and HoxH) are also found in the well-described related enzyme from Ralstonia eutropha. The fifth one (HoxE) is not encoded in the R. eutropha genome, but shares homology with the N-terminal part of R. eutropha HoxF. However, in cyanobacteria, HoxE contains a 2Fe-2S cluster-binding motif that is not found in the related R. eutropha sequence. In order to obtain some insights into the role of HoxE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…The authors discussed that under anoxia, the reduced NADPH pools may be consumed by the bidirectional Hox hydrogenase [35]. Contrarily, studies on HoxE deletion strain suggested better performance of NADH over NADPH, as electron donors to the bidirectional Hox hydrogenase in Synechocystis [78]. H/D exchange rates conducted on soluble wild type cell extracts indicated that NADH was a much better electron donor compared to NADPH, however for the HoxE deletion mutant, supplementation of the soluble extract with NADPH showed higher activity.…”
Section: Key Advances In Cyanobacterial Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors discussed that under anoxia, the reduced NADPH pools may be consumed by the bidirectional Hox hydrogenase [35]. Contrarily, studies on HoxE deletion strain suggested better performance of NADH over NADPH, as electron donors to the bidirectional Hox hydrogenase in Synechocystis [78]. H/D exchange rates conducted on soluble wild type cell extracts indicated that NADH was a much better electron donor compared to NADPH, however for the HoxE deletion mutant, supplementation of the soluble extract with NADPH showed higher activity.…”
Section: Key Advances In Cyanobacterial Researchmentioning
confidence: 99%
“…H/D exchange rates determine the turnover of the catalytic site independently of the electron transfer. This led the authors to conclude that whereas NADH-mediated interaction occurred via the diaphorase moiety, the NADPH interaction occurred through an alternate mechanism [78]. Although it was generally accepted that the pyridine nucleotides were involved in transport of electrons to the Hox hydrogenase, there was general confusion regarding the nature; NADPH or NADH.…”
Section: Key Advances In Cyanobacterial Researchmentioning
confidence: 99%
See 3 more Smart Citations